Iron Oxide Nanoparticle-Induced Autophagic Flux Is Regulated by Interplay between p53-mTOR Axis and Bcl-2 Signaling in Hepatic Cells - Uzhytchak, Mariia; Smolková, Barbora; Lunova, Mariia; Jirsa, Milan; Frtús, Adam; Kubinová, Šárka; Dejneka, Alexandr; Lunov, Oleg (Cells, 2020)
Iron oxide-based nanoparticles have been repeatedly shown to affect lysosomal-mediated signaling. Recently, nanoparticles have demonstrated an ability to modulate autophagic flux via lysosome-dependent signaling. However, the precise underlying mechanisms of such modulation as well as the impact of cellular genetic background remain enigmatic. In this study, we investigated how lysosomal-mediated signaling is affected by iron oxide nanoparticle uptake in three distinct hepatic cell lines. We found that nanoparticle-induced lysosomal dysfunction alters sub-cellular localization of pmTOR and p53 proteins. Our data indicate that alterations in the sub-cellular localization of p53 protein induced by nanoparticle greatly affect the autophagic flux. We found that cells with high levels of Bcl-2 are insensitive to autophagy initiated by nanoparticles. Altogether, our data identify lysosomes as a central hub that control nanoparticle-mediated responses in hepatic cells. Our results provide an important fundamental background for the future development of targeted nanoparticle-based therapies.
Keywords: nádorový supresorový protein p53; autofagie; Cell Line; Hepatocytes; Lysosomes; Magnetic Iron Oxide Nanoparticles; lidé; Autophagy; lysosomes; Tumor Suppressor Protein p53; magnetické nanočástice oxidů železa; magnetic resonance imaging; nano-bio interactions; p53; hepatocyty; Humans; Proto-Oncogene Proteins c-bcl-2; TOR Serine-Threonine Kinases; TOR serin-threoninkinasy; autophagy; lyzozomy; buněčné linie; iron oxide nanoparticles; protoonkogenní proteiny c-bcl-2